Analisis Model Problem Based Learning dalam Pembelajaran Abad 21 dari Segi Karakteristik Peserta Didik - Arissandi, Nopi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The development of the times is getting faster, changing attitudes and patterns of human thinking. Likewise, the characteristics of students also experience changes. The role of education is very important in preparing students to have 21st century skills. One of the efforts to face the challenges of 21st century learning is to change the teacher's role from providing and delivering information to being a facilitator to share information and practice problem solving skills to students. Constructivism approach is one of the alternatives in 21st century learning. Problem Based Learning learning model is one of the most popular models in constructivism approach. However, there are still many educators who experience confusion in implementing these learning steps. And answer whether the model is in accordance with the character of 21st century students.